2014
DOI: 10.1186/1756-9966-33-52
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of selective MEK1/2 inhibitor AZD6244 in combination with PI3K/mTOR inhibitor BEZ235 in gefitinib-resistant NSCLC xenograft models

Abstract: PurposeAlthough the EGF receptor tyrosine kinase inhibitors (EGFR-TKI) gefitinib have shown dramatic effects against EGFR mutant lung cancer, patients become resistant by various mechanisms, including gatekeeper EGFR-T790M mutation, MET amplification, and KRAS mutation, thereafter relapsing. AZD6244 is a potent, selective, and orally available MEK1/2 inhibitor. In this study, we evaluated the therapeutic efficacy of AZD6244 alone or with BEZ235, an orally available potent inhibitor of phosphatidylinositol 3–ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 36 publications
4
38
0
Order By: Relevance
“…It was shown that AZD6244 was not effective at inhibiting H460 injected athymic nude mice tumors. However, AZD6244 and BEZ235 combination reduced cell viability and tumor volume [40]. Hata et al determined MEK and PI3K inhibitor combinations do not cause apoptosis in most human KRAS mutant NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that AZD6244 was not effective at inhibiting H460 injected athymic nude mice tumors. However, AZD6244 and BEZ235 combination reduced cell viability and tumor volume [40]. Hata et al determined MEK and PI3K inhibitor combinations do not cause apoptosis in most human KRAS mutant NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…While therapies targeting EGFR and, more recently, ALK are effective in treating tumors that harbor molecular alterations, there is heterogeneity in results due to the complexity of signaling pathways involved both in oncogenesis and in acquired resistance. Therefore, analyses of other molecular signatures and profiles in protein expression may be critical in understanding the development in effective new drugs and combinations [ 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the downstream molecules Akt and the signal transduction and activator of transcription (STAT), which promotes cell survival, may be responsible for resistance to apoptosis induced by therapies [ 13 ]. Another pathway that may act in the inhibition of apoptosis is the ERK1/2 pathway [ 11 , 14 , 15 ]. Furthermore, enzyme repair cross-complementation group 1 (ERCC1) also plays a key role in excision repair enzyme pathways and its expression has been suggested to correlate with survival in lung carcinomas, as well as predicting sensitivity to platinum-based chemotherapy [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antiangiogenic role of another MEK inhibitor, Selumetinib, was previously reported in lung cancer cells resistant to anti-EGFR therapies [29]. Further, Trametinib demonstrated an anti-angiogenetic activity also in HUVEC cells but not in in vivo model of renal cell carcinoma [30].…”
Section: Discussionmentioning
confidence: 95%